Answer: x = Π/3
Step-by-step explanation:
From trigonometry identity,
sin²x + cos²x = 1
sin²x = 1 - cos²x ... (1)
Given the equation,
2sin²x−5cosx+1=0 ... (2)
Substituting equation 1 into 2, we will have;
2(1-cos²x)-5cos(x)+1 = 0
2-2cos²x-5cos(x)+1 = 0
-2cos²x-5cos(x)+3 = 0
Multiplying through by minus will give;
2cos²x+5cos(x)-3 = 0
Let P = cos(x)... (3)
The equation will become;
2P²+5P-3 = 0
Factorizing the equation gotten, we have;
2P²+6P-P-3 = 0
2P(P+3)-1(P+3) = 0
(2P-1)(P+3) = 0
2P-1 = 0; P = 1/2
P+3 = 0; P = -3
Therefore P = 1/2 and -3
Substituting the value of P in equation 3, we have;
cos(x) = 1/2
x = arccos1/2
x = 60° = Π/3
Since the second value of P is negative, it gives no solution so we will neglect it.
Therefore, x = Π/3 for 0<x<2Π